On the ecology of bumble bees of the Talysh Region, Azerbaijan (Hymenoptera, Apoidea, Bombus). - Aliev, Halid A. (Contributions to Entomology = Beiträge zur Entomologie, 2005)
The Caucasian isthmus, which began to take shape in the tertiary period, is characterised by the presence of various plants and animals both of boreal and tropical origin. These characteristic species are mostly endemic. They are concentrated in the mountain systems of the Greater and Lesser Caucasus and alsoTalysh. The bumble bee fauna of Talysh contains 22 species belonging to two ecological groups : mesophile - Bombus lucorum L., B. zonatus apicalis Skor., B. daghestanicus Rad., B. eriophorus caucasicus Rad. and xerophile species of the high mountains and steppes, most of which are endemic - B. argillaceus Scop., B. simulatilis Rad., B. armeniacus Rad., B. alboluteus Pal., B. vorticosus Gerst., B. mlokosiewitzii Rad., B. incertus Mor., B. persicus Rad., B. melanurus Lep. Keywords Bombus, species diversity, distribution, ecology, foodplants.